1990
DOI: 10.1063/1.346891
|View full text |Cite
|
Sign up to set email alerts
|

Modulation effects near the GaAs absorption edge

Abstract: We show that the large features often found below the band gap in modulated spectra of GaAs samples are linked not only to impurities but also to back-surface reflection effects. Their proximity to the band edge depends on the geometry of the cavity in which the multiple reflections occur, the impurity species, and the temperature. Impurity contributions to the energy-dependent absorption coefficient become manifest in a multiple-reflection-enhanced reflectance edge. Externally applied perturbations modulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Effects of the back-surface reflections Before presenting the temperature-dependent spectroscopic data, let us consider the role of BSR on modulated reflectance spectra in more detail. Previously, the BSR effect on PR spectra has been studied for GaAs, 19,20 but not for QD structures. The probability of an absorption process occurring in the QD layer is defined by the absorption crosssection, r ¼ a/N, where a is absorption coefficient and N is the QD sheet density.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of the back-surface reflections Before presenting the temperature-dependent spectroscopic data, let us consider the role of BSR on modulated reflectance spectra in more detail. Previously, the BSR effect on PR spectra has been studied for GaAs, 19,20 but not for QD structures. The probability of an absorption process occurring in the QD layer is defined by the absorption crosssection, r ¼ a/N, where a is absorption coefficient and N is the QD sheet density.…”
Section: Resultsmentioning
confidence: 99%
“…The 3.466-eV peak can be decomposed into two peaks at 3.467 eV and 3.455 eV. We attributed these peaks to a neutral donor bound exciton 12 and a neutral acceptor bound exciton, 11 respectively. The neutral donor is likely Si Ga , 16,17 since the sample was doped with Si.…”
Section: ͑1͒mentioning
confidence: 99%
“…However, other experiments showed that BLS resulted from back surface reflection effects. 9,10 Tober et al 11 attributed the BLS in their GaAs samples to both impurities and back surface reflections.…”
mentioning
confidence: 99%
“…2 is due to the mechanism of back surface reflection effects ͑BSR͒ of the modulation spectra. 12,13 In the influence of BSR, the contribution of the imperfection to the energy-dependent absorption coefficient became manifest in a multiple-reflection-enhance reflectance edge. 13 From Fig.…”
mentioning
confidence: 99%
“…12,13 In the influence of BSR, the contribution of the imperfection to the energy-dependent absorption coefficient became manifest in a multiple-reflection-enhance reflectance edge. 13 From Fig. 2, the energies of E D1 , E D2 , E D3 , E D4 , E D6 , and E D8 in the PzR spectra show the temperature-insensitive character at 15 and 300 K. These features are most probably related to the transitions of dangling bond to dangling bond or dangling bond to conduction-band bottom ͑E C ͒ of a-SiN x .…”
mentioning
confidence: 99%